Qualitative phytochemical screening, antioxidant activity, and antimicrobial activity of Paspalum scrobigulatum crude methanolic extract and solvent fractions - Cesar, Jedaiah Hannah R.; Fuentes, Rolly G. (2023)
Plant-based medicines are one of the leading approaches to manufacture more efficient and nontoxic pharmaceuticals that provide little to no adverse effects towards humans. Paspalum scrobiculatum, or Bias-Biasan, is a perennial grass that is commonly classified as weed in the agriculture sector; however, can serve as a major crop or famine food to countries such as India and Africa. P. scrobiculatum samples were extracted with absolute methanol through 24 h maceration extract: n-hexane, ethyl acetate, and aqueous. Qualitative phytochemical screening was conducted to the crude methanolic extract and solvent fractions, which exhibited presence and/or traces of phenols, tannins, saponins, flavonoids, and carbohydrates. The antioxidant activity of the samples were determined using the phosphomolybdenum method. The crude methanolic extract exhibited the highest total antioxidant content (112.57 +/- 0.032 ug/mL), followed by the ethyl acetate (53.484 +/- 0.057 ug/mL), n-hexane (44.397 +/- 0.136 ug/mL), and aqueous fractions (29.74 +/- 0.004 ug/mL). The presence of the phenolic compounds, tannins, flavonoids, and phenols, primarily contributed to the antioxidant potential of the samples. Antimicrobial susceptibility test was performed through Kirby-Bauer Disk Diffusion Assay methods. The crude methanolic extract and solvent fractions were tested against Staphylococcus aureus, Escherichia coli, and Aspergillus niger. No significant antimicrobial activity were observed from the crude extract and fractions. Therefore, no active antimicrobial components are present in all of the extracts.
Undergraduate thesis (BS Biology) -- University of the Philippines, Tacloban.